Jack and Jill - Alcott, Louisa May, 1832-1888. (Boston, Mass. : Little, Brown, 1999)
When friends Jack and Jill are injured in a sledding accident, their family and friends rally around them to help in their recovery.
"From the original publisher."
Keywords: Family life -- Fiction; Friendship -- Fiction; Winter -- Fiction